Y A-T-Il Une Relation Entre Teneur En Chlorophylle Et Accumulation De La Proline Chez Les Céréales À Paille Sous Déficit Hydrique? - Merabta Sarra; Zerafa Chafia; Benlaribi Mostefa (European Scientific Journal, ESJ, 2018)
This paper focuses on the relationship between two genotypes of durum wheat (Triticum durum Desf.): Gamgoum Rekham (GGR) and Haurani; two genotypes of common wheat (Triticum aestivum L.): Florence aurore 8193 (FA) and Mexipak; and two genotypes of barley (Hordeum vulgare L.): Manel and Saïda 183. These genotypes were subjected to a water deficit during a period of twenty days at the heading stage. The proline content and the chlorophyll content are determined on the standard leaves both on the control and on the sample subjected to water stress after twenty days and after one and two weeks, following the return of watering. Despite the fact that these varieties are cultivated under the same conditions on the Algerian highlands, their reactions to the test conditions are very different. As a matter of fact, GGR and FA recorded very high levels of proline at the end of the stress. This, however, was at the moment when the two barley genotypes presented relatively low values for the two studied parameters. After the return of watering, the proline contents at the various genotypes returned gradually to those of the controls. The GGR genotype recovers more quickly than the others. As for the chlorophyll content, it evolves, unevenly, in the course of the test, showing no evolutionary indication in relation to the proline.